Factors associated with therapeutic non-compliance among type 2 diabetes mellitus patients in Chidambaram, Tamilnadu, India - M., Manobharathi; P., Kalyani; Felix A., John William; A., Arulmani (International Journal Of Community Medicine And Public Health, 2017)
Background: Diabetes mellitus is one of the most common non-communicable diseases causing many serious complications worldwide. Therapeutic non-compliance leads to treatment failure thus making diabetes a serious problem to both the individuals and the health care providers. There are many factors which influence patient’s compliance. The aim of this study is to assess the frequency of therapeutic compliance and factors associated with therapeutic non-compliance. Methods: A descriptive cross-sectional study was conducted among type 2 diabetes mellitus patients attending the urban health centre, Chidambaram. Compliance and factors associated with non-compliance were assessed using Morisky Medication adherence questionnaire. Results: 108 diabetic patients were enrolled. The overall compliance rate was found to be 39.8%. A statistically significant association was found between non-compliance and associated chronic diseases (p=0.007), financial problems to buy the medicines (p=0.001), reporting side effects with the prescribed medicines (p=0.049), missed at least one dose in last one week(p=0.01). Conclusions: Majority of the patients were non-compliant. This emphasizes the need of strengthening health system and improving patients knowledge through teaching programs.